Stay or leave? The impact of cities’ air quality on the settlement intention of urban migrants: empirical evidence from China - Hengyi, Liu; Zeyu, Zhang; Zixiang, Luo; Wei, Chen (Frontiers in Environmental Science, 2025)
As a widespread environmental problem, the relationship between the air pollution and the intention of urban migrant populations to stay in cities has been discussed more limited at the micro level. We investigate the effects of air pollution on the willingness of migrant population to settle down by Probit model, based on the data from 2017 to 2018 in China Migrants Dynamic Survey (CMDS). The results of the study show that an increase of 100 units in the AQI leads to a significant decrease of approximately 13.25 percentage points in the settlement intention of urban migrants. This effect exhibits notable heterogeneity, with air pollution having a particularly negative impact on males, married groups, middle-aged and elderly people over 50 years old, those engaged in agriculture, forestry, animal husbandry and fishery, and high-income groups. In addition, this paper further examines the mechanism by which air pollution reduces the willingness of migrants to stay, and finds that air pollution affects the settlement intention mainly by reducing health status, labour time and wage income. Moreover, the urban green coverage can mitigate air pollution’s negative impact on migrants’ settlement intention. Air pollution not only undermines investment in human capital, but may also be an impediment to sustainable urban development. Therefore, this study can provide a new perspective for urban development and human capital accumulation.